Manajemen Madrasah Aliyah dalam Menghadapi Era Society 5.0 - Astuti, Puji; Suklani (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
Currently we have entered the era of Society 5.0 where this era was born as a result of the Industrial Revolution 4.0 which made the role of humans slightly reduced due to technology. Society 5.0 has entered all sectors, including education. Educational institutions are a place to gain knowledge. This research aims to present a comprehensive overview of Madrasah Aliyah's steps in preparing for the Society 5.0 era. Library study (library research) as a research method. Data comes from the literature regarding this research topic. Meanwhile, scientific articles, proceedings, theses, and these are data sources. Observation as a data collection technique. 27-3 December 2023 was used for data collection. The research location is optional. The research results show that Madrasah Aliyah must make various efforts to face the era of Society 5.0, including the role of the head of the Madrasah Aliyah in the educational unit, the competence of educators, and 21st-century learning. Readers can build awareness of the importance of the competencies needed to face the era of Society 5.0. Of course, this is useful so that Indonesian human resources form strong, intellectual, and skilled personalities.